Association between change in serum bicarbonate and change in thyroid hormone levels in patients receiving conventional or more frequent maintenance haemodialysis. Issue 1 (16th December 2018) - Molfino, Alessio; Beck, Gerald J; Li, Minwei; Lo, Joan C; Kaysen, George A
ABSTRACT: Aim: Correction of metabolic acidosis in patients with chronic kidney disease has been associated with improvement in thyroid function. We examined whether changes in bicarbonate were associated with changes in thyroid function in patients with end‐stage renal disease receiving conventional or more frequent haemodialysis. Methods: In the Frequent Hemodialysis Network Trials, the relationship between changes in serum bicarbonate, free triiodothyronine (FT3) and free thyroxine (FT4) was examined among 147 and 48 patients with endogenous thyroid function who received conventional (3×/week) or more frequent (6×/week) haemodialysis (Daily Trial) or who received conventional or more frequent nocturnal haemodialysis (Nocturnal Trial). Equilibrated normalized protein catabolic rate (enPCR) was examined to account for nutritional factors affecting both acid load and thyroid function. Results: Increasing dialysis frequency was associated with increased bicarbonate level. Baseline bicarbonate level was not associated with baseline FT3 and FT4. Change in bicarbonate level was not associated with changes in FT3 and FT4 in the Daily Trial nor for FT4 in the Nocturnal Trial (r ≤ 0.14, P > 0.21). While, a significant correlation between change in serum bicarbonate and change in FT3 (r = 0.44, P = 0.02) was observed in the Nocturnal Trial; findings were no longer significant after adjusting for change in enPCR (r = 0.37, P = 0.08). For participants with baseline bicarbonate <23 mmol/L, no association between change in bicarbonate and change in thyroid indices were seen in the Daily Trial; for the Nocturnal Trial, findings were also not significant for change in FT3 and the association between change in bicarbonate and change in FT4 (r = 0.54, P = 0.03) was no longer significant after adjusting for enPCR (r = 0.45, P = 0.11). Conclusion: Changes in bicarbonate were not associated with changes in thyroid hormone levels after adjusting for enPCR, as a marker of nutritional status. Future studies should examine whether improvement in acid base status improves thyroid function in haemodialysis patients with evidence of thyroid hypofunction. Summary at a Glance: There have been several reports to suggest a contributing role of metabolic acidosis in altering thyroid function. However, in this study, changes in serum bicarbonate levels in HD patients were not associated with changes in thyroid hormone levels after adjusting for a marker of nutritional status.